Działania na rzecz aktywizacji zawodowej i społecznej młodzieży z niepełnosprawnością intelektualną – projekt warszawskiego modelu współpracy - Serafin, Teresa (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
The article presents background information that explains the reason for the establishment of the Warsaw Initiatives for People with Intellectual Disabilities and a conjugated. Includes justification for action and presents information obtained as a result of the audit. The aim of the group is: understanding the needs of professional and social activation graduates of schools, institutions and develop the model project of the Information and Coordination Point for People with Disabilities in Warsaw. Recognizing the needs of graduates was carried out in schools and institutions in cooperation with the Office of Education. From the conclusions of respondents in Warsaw no common for the whole city, the system information about the various services provided to people with intellectual disabilities or multiple disabilities. Central place whose main purpose would be providing up to date information on all forms provided in support tailored to the needs and abilities of the person concerned could become a point of the Information and Coordination